2023
DOI: 10.3389/fvets.2023.1138419
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiological investigation of group A porcine rotavirus in East China

Abstract: Group A porcine rotavirus (RVA) is a serious threat to the breeding industry worldwide, which was associated with severe diarrhea in piglets. However, the prevalence and molecular characterizations of RVA circulating in farms of East China remains largely unknown. Five hundred and ninety-four samples were collected from 35 farms in East China from September 2017 to December 2019. The results showed that 16.8% was positive for RVA of all samples. Among different types of samples, the highest positive rate of RV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 34 publications
4
16
0
Order By: Relevance
“…PoRV is the second most common viral pathogen causing diarrhea in pigs. The 13 PoRV strains in this study were dominated by the G9 genotype, accounting for 61.54% of the total, followed by the G5 genotype, accounting for 15.38% of the total, which was consistent with the results of the previous study ( Tao et al, 2023 ). Papp et al collected and screened 77 original articles from various regions between 1976 and 2011 to investigate the distribution of porcine rotavirus group A genotypes.…”
Section: Discussionsupporting
confidence: 92%
“…PoRV is the second most common viral pathogen causing diarrhea in pigs. The 13 PoRV strains in this study were dominated by the G9 genotype, accounting for 61.54% of the total, followed by the G5 genotype, accounting for 15.38% of the total, which was consistent with the results of the previous study ( Tao et al, 2023 ). Papp et al collected and screened 77 original articles from various regions between 1976 and 2011 to investigate the distribution of porcine rotavirus group A genotypes.…”
Section: Discussionsupporting
confidence: 92%
“…Our results presented in this study demonstrated a complex condition on the prevalence of RVA on Chinese pig farms, as evidenced by the characterization of 10 RVA genotypes. Among these genotypes, G9, G5, and G4 were the predominantly characterized genotypes, which agrees well with the other reports from both China and other countries [ 41 , 42 ], indicating an active role these genotypes in promoting swine diarrhea.…”
Section: Discussionsupporting
confidence: 91%
“…Epidemiological survey data have shown that PoRVA is endemic and widespread in large-scale pig farms worldwide [ 15 , 16 ]. Until now, there has been no nationwide epidemiological investigation specifically targeting multiple genes of PoRVA in China, except a few studies that reported the positive rate of pig samples and farms in individual provinces [ 21 , 22 , 23 ]. For instance, a study conducted from 2013 to 2019 reported an RVA positive rate of 7% in Zhejiang, Shandong, Jiangsu and Shanxi provinces [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a study conducted from 2013 to 2019 reported an RVA positive rate of 7% in Zhejiang, Shandong, Jiangsu and Shanxi provinces [ 24 ]. Another study conducted from 2017 to 2019 found an RVA positive rate of 16.83% (100/394) in East China [ 23 ]. In 2022, a study conducted in Heilongjiang province reported an RVA positive rate of 4.3% (12/280) [ 25 ].…”
Section: Discussionmentioning
confidence: 99%